SOLAR SOFTWARE APPLIED TO DESIGN A PHOTOVOLTAIC SYSTEM TO SUPPLY THE ENERGY DEMAND OF AN ITALIAN SCHOOL - Laranci, P.; Silveira, J. L.; Lamas, W. Q. (Revista de Engenharia Térmica, 2009)
This paper has as objective to describe the use of SOLAR 1.1 software to design a system for supplying a part of the electric demand of a school situated in Umbertide, comparing the use o SOLAR 1.1 to real results of a system implanted yet. This software version helps also to conduce the economic analysis for grid connected or standalone photovoltaic systems for the choice of convenient values of investment rate and annuity factor and it calculates the payback period of investment in the photovoltaic plant.